2013
DOI: 10.3855/jidc.3068
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus detection in Moroccan patients with bladder cancer

Abstract: Introduction: Human papillomavirus (HPV) is associated with more human cancers than any other virus. Many studies have investigated the association between bladder cancer and HPV but the results remain controversial. The aim of the present study is to evaluate whether HPV have an etiological role in bladder carcinogenesis among Moroccan patients. Methodology: Forty-eight fresh biopsies (43 bladder tumors and 5 non-tumor samples) were collected for this purpose. Nested PCR with the consensus MY09/MY11 and GP5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…High-risk HPVs are the primary causative agents of carcinomas (32). The prevalence of high-risk HPV in BC varies, particularly in Moroccan patients, with the highest prevalence of 52.4% (33). However, clinical trials have reported that HPV is not associated with the risk of BC (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…High-risk HPVs are the primary causative agents of carcinomas (32). The prevalence of high-risk HPV in BC varies, particularly in Moroccan patients, with the highest prevalence of 52.4% (33). However, clinical trials have reported that HPV is not associated with the risk of BC (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated that HPV16/18 infection probably participated in the occurrence of transitional cell carcinoma of the bladder and had a certain influence on the malignancy and progression of the disease. Berrada et al [12] conducted a test over the high-risk HPV DNA in the tumor tissue of 45 bladder cancer patients from Morocco. The results implied that high-risk HPV infection, especially HPV16 infection, was related to the occurrence and development of bladder cancer.…”
Section: High-risk Hpv Infection and Bladder Cancermentioning
confidence: 99%
“…HPV16, and to a lesser extent HPV18, were the most common HPV types in cancer tissue [52] . Geographic variation was striking as evidenced by two studies from North Africa with HPV DNA was detected in 22 (52.4%) of 43 of fresh bladder cancers from Moroccan patients whereas HPV DNA was not detected in any of 125 formalin fixed bladder cancers among Tunisian patients [56,57]. One study found that HPV risk for bladder cancer was greater than for non-smokers [58].…”
Section: Bladder Cancermentioning
confidence: 99%